Application of Religious Moderation Values to Serambi Darussalam IT Junior High School Students - Seriani (Jurnal Profesi Guru Indonesia, 2024)
This article aims to examine in depth the role of Islamic Religious Education Teachers in instilling the values ​​of religious moderation in students at SMP IT Darussalam Kampung Uning Gelung, Dabun Gelang District, Gayo Lues Regency, as well as analyzing its implementation and implications. A qualitative approach is used with data collection techniques through interviews, observations, and documentation of Islamic Religious Education Teachers, School Principals, learning processes, and interactions in the school environment. The results of the research show that Islamic Religious Education Teachers have a very important role, including setting an example of mutual respect and tolerance towards religious differences, providing an understanding of religious moderation through an interactive and participatory learning model in the classroom, as well as playing a role in creating good social interaction between students of different religions by upholding mutual respect, respect and tolerance. The implementation of cultivating an attitude of religious moderation is done through three ways, namely the learning process in the classroom, interaction in the school environment, and the school's interaction with the surrounding environment. In the implementation, it is seen that students respect each other and uphold tolerance in accordance with the values ​​of religious moderation taught. The implication is that the school policy is non-discriminatory in providing the right to religious education for all students, as well as creating a sense of tolerance in students in a wider social life. The researcher concluded that teachers play a strategic role in instilling religious moderation through good example, learning, and social interaction. With proper implementation and supportive school policies, this effort has a positive impact on a more tolerant and harmonious social life.